Clinical characteristics of acute lower respiratory tract infections due to 13 respiratory viruses detected by multiplex PCR in children - Jeong-Sook Lim; Sung-Il Woo; Hyuk-Il Kwon; Hyuk-Il Kwon; Young-Ki Choi; Youn-Soo Hahn (Korean Pediatric Society, 2010)
Purpose : This study was performed to investigate the epidemiologic and clinical features of 13 respiratory viruses in children with acute lower respiratory tract infections (ALRIs). Methods : Nasopharyngeal aspirates were prospectively obtained from 325 children aged 15 years or less from May 2008 to April 2009 and were tested for the presence of 13 respiratory viruses by multiplex real-time-polymerase chain reaction (RT-PCR). Results : Viruses were identified in 270 children (83.1%). Co-infections with ?#242; viruses were observed in 71 patients (26.3 %). Respiratory syncytial virus (RSV) was the most common virus detected (33.2%), followed by human rhinovirus (hRV) (19.1%), influenza virus (Flu A) (16.9%), human metapneumovirus (hMPV) (15.4%), parainfluenza viruses (PIVs) (8.3%), human bocavirus (hBoV) (8.0%), adenovirus (ADV) (5.8%), and human coronavirus (hCoV) (2.2%). Clinical diagnoses of viral ALRIs were bronchiolitis (37.5%), pneumonia (34.5%), asthma exacerbation (20.9%), and croup (7.1%). Clinical diagnoses of viral bronchiolitis and pneumonia were frequently demonstrated in patients who tested positive for RSV, hRV, hMPV, or Flu A. Flu A and hRV were most commonly identified in children older than 3 years and were the 2 leading causes of asthma exacerbation. hRV C was detected in 14 (4.3%) children, who were significantly older than those infected with hRV A (mean±SD, 4.1±3.5 years vs. 1.7±2.3 years; P=0.009). hBoV was usually detected in young children (2.3±3.4 years) with bronchiolitis and pneumonia. Conclusion : This study described the features of ALRI associated with 13 respiratory viruses in Korean children. Additional investigations are required to define the roles of newly identified viruses in children with ALRIs.